The students’ responses on integrating online corpus and online dictionary to expand English vocabulary for tourism - Andi Rizki Fauzi (Universitas Ahmad Dahlan)
Vocabulary is considered as the most essential part for students in English learning including those who are learning English for Tourism. The reason behind this is that nothing can be conveyed both in written or spoken language without vocabulary. Some researchers attempted to apply some strategies and approaches to assist the students in gaining vocabulary mastery. One of the ways is by using a corpus-based approach. However, to understand the corpus data need huge effort if the students have a lack of vocabulary due to the complexity of the language used. For that reason, the use of the online dictionary is required that eases the students to seek the meaning of unfamiliar words in the corpus. The researcher aims to know the students’ responses on integrating online corpus and dictionary to expand English vocabulary for tourism after conducting experimental research to the fourth semester of hospitality students in 8 meetings. In the treatments given, the researcher only focused on 100 words which were considered as unfamiliar words selected from articles in tourism fields. The questionnaires were distributed to recognize what they perceived after the integration of online corpus and the online dictionary. The result showed that the students responded positively to the use of the online dictionary while learning vocabulary through online corpus as the students could understand the corpus data presented better than without the use of online dictionary and they could broaden their vocabulary.